(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In the current experimental investigation, 100% quarry dust is used in place of natural sand to create concrete with grades of M40. The primary source of worry is the non-renewable quality of natural sand and the building industry’s rising demand for it. River sand, one of the primary components used to make concrete, is becoming more costly and rare. It is now necessary to search for an alternative to river sand. Therefore, quarry dust may be substituted for river sand in many applications. Quarry dust is recognised as a construction material because it has characteristics with river sand. The goal of the current study is to determine the highest amount of quarry dust that may replace river sand in M40 mix designations, with equal percentages ranging from 0% to 50%. The slump cone technique is used to determine viability. To find the concrete’s compressive strength, tests are carried out using cubes formed in each percentage.